Национальная цифровая платформа: перспективы создания в Украине - Вишневский, А.С. (Вісник економічної науки України, 2020)
В останні десятиліття триває поглиблення процесів цифровізації, які значною мірою базуються на розвитку цифрових платформ і розширенні ступеня їх проникнення в соціально-економічну сферу. Хоча особливу роль займають великі цифрові платформи, які іноді об'єднують мільярди користувачів, поки не оформився окремий клас – національні цифрові платформи. Тому метою роботи є обґрунтування перспектив створення національної цифрової платформи в Україні. В рамках дослідження дано визначення національної цифрової платформи. Показано відсутність фундаментальних причин, що перешкоджають її формуванню. У числі основних завдань, вирішення яких забезпечує можливості для створення національної цифрової платформи в Україні, визначені: підключення всього населення до мережі Інтернет; забезпечення всього населення пристроями доступу до мережі Інтернет; забезпечення достатнього рівня цифрової грамотності всього населення країни. В последние десятилетия продолжается углубление процессов цифровизации, которые во многом базируются на развитии цифровых платформ и расширении степени их проникновения в социально-экономическую сферу. Хотя особую роль занимают большие цифровые платформы, иногда объединяющие миллиарды пользователей, пока не оформился отдельный класс – национальные цифровые платформы. Поэтому целью роботы является обоснование перспектив создания национальной цифровой платформы в Украине. В рамках исследования дано определение национальной цифровой платформы. Показано отсутствие фундаментальных причин, препятствующих её формированию. В числе основных задач, решение которых обеспечивает возможности для создания национальной цифровой платформы в Украине, определены: подключение всего населения к сети Интернет; обеспечение всего населения устройствами доступа к сети Интернет; обеспечение достаточного уровня цифровой грамотности всего населения страны. In recent decades, the deepening of digitalization processes continues, which are largely based on the development of digital platforms and the expansion of their penetration into the socio-economic sphere. Although large digital platforms, sometimes uniting billions of users, play a special role, until a separate class has emerged – national digital platforms. Therefore, the purpose of the robot is to justify the prospects of creating a national digital platform in Ukraine. In the framework of the study, the national digital platform is defined as a single set of registers of legal entities and individuals, public authorities and public services, algorithms for their interaction and storage, registries and transactions carried out between them, which operates online and is owned by the state.
Among the problems associated with the creation and operation of big digital platforms, the following were highlighted: the need for significant initial investment to create a big digital platform; digital dictatorship (both from the state and society); monopolization and restriction of real competition due to the scale of the digital platform; security of data storage (primarily personal); using confidential data to gain competitive advantage and additional income; discrimination of platform users; general access to the Internet for individuals and legal entities, as well as government bodies. These problems are not critical for the formation of a nationwide digital platform in Ukraine. The main problem is the lack of social Internet and devices that provide Internet access for the entire population. Therefore, among the main tasks, the solution of which provides for creating a national digital platform in Ukraine, the following are identified: connection of the entire population to the Internet; providing the entire population with Internet access devices; ensuring a sufficient level of digital literacy for the entire population of the country.